'A Blessed and Glorious Work of God, … Attended with Some Irregularity': Managing Methodist Revivals, c.1740–1800. (June 2021) - Norris, Clive Murray
Abstract : The Connexion established by John Wesley (1703–91) experienced many outbreaks of local revival in the late eighteenth century. These were examples of the tension between reason and emotion, spontaneity and regularity, which characterized the movement. This article discusses how, amidst concerns from within Methodism and beyond, the leadership sought to manage but not suppress what was perceived to be this work of the Holy Spirit. Its challenge to the connexional polity was especially acute in the 1790s, during the Great Yorkshire Revival. In 1800, a Methodist-inspired publication sought to present good practice on validating and encouraging local revivals while maximizing their effectiveness and minimizing any disruption to the connexional order or wider civil society. However, despite fears that institutional concerns were dampening the Spirit's work, around 1800 Wesley's successors acted to reassert the control of the Preachers' Conference over Methodist practice and premises, and a cautious rationalism came to the fore.